Odpowiedzi

2010-03-04T18:01:45+01:00
A) 9y + 5 + (2y + 3x - y) - 10y=9y+5+2y+3x-y-10y=3x+6
b) (3 - 4x² + 5x² + 3)=3-4x²+5x²+3=x²+6
c) (4a² - 3ab - 0,1a) + (-14a² + 2ab + 0,1a)=4a² - 3ab - 0,1a-14a²+2ab+0,1a=-10a²-ab
2010-03-04T18:01:54+01:00
A) 9y+5+(2y+x-y)-10y=9y+5+2y+x-y-10y=5+x
b) (3-4x²+5x²+3)=3-4x²+5x²+3=6+x²
c) (4a² - 3ab - 0,1a) + (-14a² + 2ab + 0,1a)=
=(3,9a²-3ab)+(-13,9a²+2ab)=3,9a²-3ab-13,9a²+2ab=-10a²-ab
2010-03-04T18:02:00+01:00
A]
9y+5+(2y+3x-y)-10y=9y+5+2y+3x-y-10y=3x+5
b]
(3-4x²+5x²+3=x²+6
c]
(4a²-3ab-0,1a)+(-14a²-ab